Implementasi Manajemen Pembelajaran Inklusi Berbasis Budaya Lokal di Tk Laboratori Pedagogia UNY Yogyakarta - Mushlih, Ahmad; Munastiwi, Erni (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
Inclusion learning is a combination of learning process between normal child and special needs child, both physically and non-physically. Each educational institution has a special branding in the learning process, one of which is local culture-based inclusion. TK Laboratori Pedagogia UNY is one of the schools that carry out the learning of local culture-based inclusion in the region of Yogyakarta. The purpose of this research is expected to provide an overview of the process of implementing a local and locally-based kindergarten. This research is a qualitative study of case study approaches. Research field data retrieval using observation, interviews, documentation. The findings of the field resulted in that 1) the reason for learning local culture based inclusion due to the inclusion and cultural regulations, inclusion education needs for early childhood and special needs, and preservation of local cultures. 2) The value of local culture applied in the learning include, tepo sliro, unggah-ungguh, andhap asor, gugur gunung, welas asih, tertib, tekun, nerimo ing pandum. 3) management processes include planning, organizing, actuatting, and controlling.